Developing Analytical Exposition Texts Based on Pancasila Student Profile for Vocational High School Students Using Sigil-Flip Animation - Syarah Yasmin Mahfuzah; Luky Tiasari (Universitas Sarjanawiyata Tamansiswa, 2025)
The needs of English materials that meet English for Specific Purposes (ESP), integrate technology, and focus on writing skills are essential for vocational school students particularly those in fashion major. The aims of this research were to: (1) describe the needs of eleventh-grade fashion students at SMK Muhammadiyah 4 Yogyakarta in English writing skills, (2) describe the development of the analytical exposition texts, and (3) describe the appropriateness of the analytical exposition texts materials developed. The research applied a Research and Development (R&D) model by Borg and Gall and simplified it into four steps, needs analysis, planning, material development, and expert judgement. The participants of the research were eleventh-grade fashion students from SMK Muhammadiyah 4 Yogyakarta. Observation, interviews, and documentation are the data collection techniques used for needs analysis. The needs analysis was served for designing a course grid and then developing a book, complemented by animated videos. Two experts validated the product using questionnaires. The evaluation results verified the appropriateness of the materials developed. The researchers conclude that, although being rarely used by fashion students, analytical exposition text can be effectively developed and utilized for fashion students, particularly through the integration of technology such as Sigil-Flip Animation and diverse methods that can enhance students' ability to write strong and logical arguments while supporting character development in line with the Pancasila student profile.